2023
DOI: 10.1108/ijchm-05-2022-0573
|View full text |Cite
|
Sign up to set email alerts
|

Family incivility, emotional exhaustion, and hotel employees’ outcomes: a moderated mediation model

Abstract: Purpose This study aims to analyze the impact of family incivility (FI) on in-role performance (IRP) and proactive customer service performance (PCSP) via the mediating effect of emotional exhaustion (EE) and the moderating roles of emotional intelligence (EI) and mindfulness. Design/methodology/approach Hypotheses were verified using multisource and multiwave data collected from 337 valid hotel employee–supervisor dyads in Kuala Lumpur, Malaysia. Data were analyzed using SPSS 24.0, AMOS 24.0 and PROCESS (ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…While extant empirical investigations have examined the negative impact of EE on job performance, scant attention has been directed toward comprehending its deleterious influence on the SRP of FLEs. For example, Yan et al (2023) observed a deterioration in both in-role and extra-role performance among hotel FLEs in Malaysia due to EE. Conversely, Yavas et al (2008) reported no significant relationship between EE and job performance in their study involving hotel FLEs in Turkey.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…While extant empirical investigations have examined the negative impact of EE on job performance, scant attention has been directed toward comprehending its deleterious influence on the SRP of FLEs. For example, Yan et al (2023) observed a deterioration in both in-role and extra-role performance among hotel FLEs in Malaysia due to EE. Conversely, Yavas et al (2008) reported no significant relationship between EE and job performance in their study involving hotel FLEs in Turkey.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Consequently, FLEs may respond negatively by reducing their SRP in order to prevent further resource depletion. Prior studies have also shown that personal and conditional resources can be effective in alleviating EE especially in the hospitality field ( Chen and Eyoun, 2021 ; Yan et al, 2023 ). Hence, we employ EE to explore the underlying mechanism linking CSE, PJ fit, and SRP.…”
Section: Introductionmentioning
confidence: 99%
“…The theory also underscores the buffering role of employees' personal and contextual resources, which will help them to protect themselves from the adverse effects of such resource-draining situations (Witt and Carlson, 2006). Anchoring on these basic tenets of COR theory, this study argues that family incivility is a chronic low-intensity stressor (Yan et al , 2023) and an adverse resource-draining situation that reduces the extra efforts required to deliver the services effectively. The study also postulates that family incivility instigates negative rumination at the workplace, which diminishes personal resources and adversely impacts better service delivery.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Hence, this study examines the conditional role of psychological capital and POS in the relationship between family incivility and negative rumination. Furthermore, Yan et al (2023) have stated that though the studies conducted in other occupational contexts have established its detrimental effects, very few studies have examined the influence of family incivility on frontline hotel FHEs’ work outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…financial stress) and nonwork (e.g. family demands) stressors (Akgunduz et al , 2023; Khawaja et al , 2022; Liu-Lastres et al , 2023; Rahimi et al , 2022; Yan et al , 2023). Work–family conflict that is composed of work interfering with family (WIF) and family interfering with work (FIW) is among these stressors (Karatepe and Karadas, 2014).…”
Section: Introductionmentioning
confidence: 99%